Edukasi Perawatan Kaki pada Pengidap Diabetes Melitus dalam Mencegah Luka Kaki di Kelurahan Sanga-Sanga Dalamm Kutai Kartanegara - Khumaidi, Khumaidi; Syahrun, Syahrun; Sukmana, Mayusef; Metungku, Fanny; Rahma, Khairunnida (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2025)
Diabetes mellitus (DM) is a chronic disease that often leads to serious complications such as diabetic foot ulcers if not properly managed. This community service activity aimed to increase knowledge and awareness of diabetic foot care among people with diabetes in Sanga-Sanga Dalam Village, Kutai Kartanegara. The program was carried out on July 23, 2025, through an educational session attended by 40 participants. The intervention included lectures, discussions, and demonstrations on proper foot hygiene, footwear selection, and adherence to treatment. Knowledge was assessed using pretest and posttest questionnaires. The results showed a significant improvement in participants’ knowledge, with an average score increase from 58.5 to 91.1 (32.6%). The findings demonstrate that structured and interactive education effectively enhances self-care abilities and preventive behaviors among diabetic patients. Continuous community-based education is essential to reduce the incidence of diabetic foot ulcers and improve quality of life.